Network pharmacology-based strategy and phytochemical screening of antioxidants suggesting the potential anti-obesity relevance of soybean food bars - Rustandi, Tedi; Hayati, Fakhriah; Nugroho, Fatah; Amalia, Senya Puteri; Nastasya, Regina; Mahal, Ahmed (Frontiers in Natural Products, 2025)
IntroductionFunctional food products are widely available in the market and have several benefits, such as high protein and low calorie content, for addressing obesity. However, the regulation of product content, which results in weight maintenance, needs to be described. This study aimed to explore methods to assess the influence of anti-obesity food bars made from soybeans on antioxidants in functional food products that are widely available in the market.MethodsThese methods include network pharmacology screening, bioactive gene analysis, interaction network development, phytochemical screening, molecular docking, and antioxidant activity testing.ResultsScreening revealed that the main bioactivities of the soybean food bars were glycitein and 6″-Omalonylglycitin, which have a high affinity for molecular docking. The food bar methanol and ethanol extracts had higher ES50 values (1.30 and 2.00 mg/mL, respectively) than genistein (0.13 mg/mL), indicating weak antioxidant activity. Therefore, the ethanol and methanol extracts of the soybean food bar exhibited weak antioxidant activity.ConclusionThis study suggests that soybean-based food bars may have potential anti-obesity relevance through predicted interactions with leptin signaling proteins, network pharmacology analysis, and measurable antioxidant activity.